2019
DOI: 10.1007/s00405-019-05732-x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking long noncoding RNA MALAT1 restrained the development of laryngeal and hypopharyngeal carcinoma

Abstract: Purpose The long non-coding RNA MALAT1 is a predictive marker in several solid tumors with highly conserved sequences. However, the role of non-coding RNA in development of laryngeal or hypopharyngeal cancer remains unclear. Methods Tumor tissues and adjacent non-cancer tissues of 24 patients were collected. We detected the expression of MALAT1 in laryngeal cancer tissues and hypopharyngeal cancer tissues. Moreover, we developed a MALAT1 silencing model in human laryngeal tumor cells by transfecting MALAT1 sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…MALAT1 has a regulatory effect on the occurrence and development of several tumors, including laryngeal, hypopharyngeal, thyroid, esophageal, lung, liver, and ovarian cancers. [30][31][32][33][34][35][36] The Relationship Between MALAT1 and HNSCC MALAT1 can regulate the occurrence and development of a variety of malignant tumors. It also plays roles in transcription, cell cycle regulation, epigenetics, and tumor metastasis.…”
Section: Malat1 Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALAT1 has a regulatory effect on the occurrence and development of several tumors, including laryngeal, hypopharyngeal, thyroid, esophageal, lung, liver, and ovarian cancers. [30][31][32][33][34][35][36] The Relationship Between MALAT1 and HNSCC MALAT1 can regulate the occurrence and development of a variety of malignant tumors. It also plays roles in transcription, cell cycle regulation, epigenetics, and tumor metastasis.…”
Section: Malat1 Structure and Functionmentioning
confidence: 99%
“…44 Inactivation of MALAT1 can inhibit gene expression regulators that modify the characteristics of laryngeal cancer and hypopharyngeal carcinoma, and blocking MALAT1 expression can inhibit the progression of both types of cancer. 33 lncRNA MALAT1 can trigger LSCC resistance to chemotherapy drugs by promoting tumor cell metastasis and inhibiting apoptosis. 43 lncRNA MALAT1 serves as a miR-429 sponge, regulating ZEB1 expression.…”
Section: The Role Of Malat1 In Hnscc Diagnosis and Progression/prognosismentioning
confidence: 99%
“…Silencing MALAT1 in human laryngeal carcinoma cell line HEp-2 and pharynx cancer cell line FaDu (RRID: CVCL_1218) can induce apoptosis and inhibit cell proliferation, resulting in cell cycle arrest in the G1/G2 phase and significant relief in the S phase. Downregulation of MALAT1 expression can also inhibit the migration and invasion of HEp-2 and FaDu (Xu E. et al, 2019). Jiang et al reported that high expression of MALAT1 can enhance the invasive ability of Tu 686 and LSC-1 (RRID: CVCL_9U29) cells, considerably improve the survival rate, facilitate proliferation, and inhibit apoptosis.…”
Section: Lncrna and Apoptosismentioning
confidence: 99%
“…Silencing MALAT1 in human laryngeal carcinoma cell line HEp-2 and pharynx cancer cell line FaDu (RRID: CVCL_1218) can induce apoptosis and inhibit cell proliferation, resulting in cell cycle arrest in the G1/G2 phase and significant relief in the S phase. Downregulation of MALAT1 expression can also inhibit the migration and invasion of HEp-2 and FaDu ( Xu E. et al., 2019 ). Jiang et al.…”
Section: Lncrna and Lscc Proliferation Migration Invasion And Apopmentioning
confidence: 99%
“…Laryngeal squamous cell carcinoma (LSCC), a common clinical malignancy of the head and neck, is a type of tumor that arises mainly from the mucosal epithelium of the larynx, accounting for approximately 5% of systemic tumors and 15% of head and neck tumors worldwide (Steuer et al, 2017;Xu et al, 2020). The main reason for shallow low 5-year survival rate, less than 50% in advanced stages of the disease, is the late diagnosis (Gourin et al, 2009;Adam et al, 2012;Brandstorp-Boesen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%